Transactions on Computational Science XXIII Special Issue on Cyberworlds - Gavrilova, Marina L.; Tan, C.J. Kenneth; Mao, Xiaoyang; Hong, Lichan (Transactions on Computational Science, 2014)
This, the 23rd issue of the Transactions on Computational Science journal, guest edited by Xiaoyang Mao and Lichan Hong, is devoted to the topic of security in virtual worlds. It contains extended versions of the best papers selected from those presented at the International Conference on Cyberworlds 2013, held at Keio University, Yokohama, Japan, October 21-23, 2013. The 11 papers in the volume have been organized into topical sections on modeling, rendering, motion, virtual environments and affective computing.